Interactions of LC8 with N-Terminal Segments of the Intermediate Chain of Cytoplasmic Dynein. (2003) - Nyarko, Afua; Hare, Michael; Makokha, Moses; Barbar, Elisar
Abstract : LC8, a highly conserved 10-kDa light chain, and IC74, a 74-kDa intermediate chain, are presumed to promote the assembly of the cytoplasmic dynein motor protein complex and to be engaged in the controlled binding and release of cargo. The interactions of LC8 from Drosophila melanogaster with constructs of IC74 were characterized in vitro by affinity methods, limited proteolysis, and circular dichroism spectroscopy. Previously, we have performed limited proteolysis on the N-terminal domain of IC74, IC(1-289), when free and when bound to dynein light chains LC8 and Tctex-1[1]. We have also shown that upon addition of LC8, IC(1-289) undergoes a significant conformational change from a largely unfolded to a more ordered structure. The purpose of the work presented here is to determine whether residues 1-30 in IC74, predicted to be in a coiled coil, are involved in the stabilization of the protein upon binding to LC8. Constructs of IC74, IC(1-143), and IC(30-143) that include the LC8 binding site but with and without the first 30 residues were prepared, and their binding and protection patterns were compared to our previous results for IC(1-289). The results suggest that coiled coil residues 1-30 are not responsible for the increase in structure we observe when IC(1-289) binds to LC8.